Evaluasi Tingkat Kapabilitas Teknologi Informasi pada STAI Auliaurrasyidin Tembilahan Menggunakan Farmework COBIT 2019 - Ansyari, Muhammad Fadli; Megawati; Saputra, Eki; Rozanda, Nesdi Evrilyan (The Indonesian Journal of Computer Science, 2025)
Information Technology (IT) plays a vital role in supporting operational efficiency and innovation, particularly in higher education. XYZ University has implemented the Integrated Academic Information System (AKSIA) to manage academic data and student services. However, technical challenges in system management require further evaluation using the COBIT 2019 framework. The evaluation focuses on DSS01 (Managed Operations), APO04 (Managed Innovation), and APO09 (Managed Service Agreements) domains, as determined through design factor analysis. Based on interviews, observations, and questionnaires analyzed using the Guttman scale and gap analysis, it was found that all domains are at Capability Level 1 with largely achieved performance: DSS01 at 75%, APO04 at 60%, and APO09 at 66%. The recommendations include improving process documentation, conducting routine monitoring of activities, and aligning services more closely with strategic needs. These steps are expected to elevate IT capability to higher levels and better support the institution's strategic objectives.